2023
DOI: 10.1101/2023.02.22.23286318
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

DNA damage, nucleolar stress and dysregulated energy metabolism as mechanisms of multimorbidity in cardiovascular disease

Abstract: Background Two-thirds of people over 65 have two or more underlying chronic conditions. Patients with multimorbidities are likely to classify as frail and have worse outcomes after cardiac surgery. We hypothesized that metabolite and transcript profiles could identify multimorbidity-specific mechanisms for clinical interventions. Methods and Results The multimorbidity was defined as two or more coexisting chronic conditions. Analysis of the metabolome was performed in 30 sequential patients. Measurements of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
(116 reference statements)
0
1
0
Order By: Relevance
“…In previous work, we have shown that MLTC are associated with myocardial changes consistent with biological ageing including altered RNA processing, DNA damage, nucleolar stress, senescence, and dysregulated energy metabolism versus non-MLTC. (48) Biological ageing processes increase susceptibility to cellular stress in experimental models. (49,50) These results identify substantial baseline heterogeneity in cardiac surgery patients at baseline and suggest that a precision medicine approach to organ protection may be required to deliver clinical benefits.…”
Section: Clinical Importancementioning
confidence: 99%
“…In previous work, we have shown that MLTC are associated with myocardial changes consistent with biological ageing including altered RNA processing, DNA damage, nucleolar stress, senescence, and dysregulated energy metabolism versus non-MLTC. (48) Biological ageing processes increase susceptibility to cellular stress in experimental models. (49,50) These results identify substantial baseline heterogeneity in cardiac surgery patients at baseline and suggest that a precision medicine approach to organ protection may be required to deliver clinical benefits.…”
Section: Clinical Importancementioning
confidence: 99%